Formulation of mycoinsecticides as water-dispersible granules for vegetable insect pest control - Chai, Ivy Ching Hsia (2011)
Microbial pesticides have been widely accepted as a biological alternative to chemical insecticides in controlling insect pests. Where disease-causing (entomopathogenic) fungi are being manipulated and used inundatively for insect pest control, such microbial pesticides are known as mycoinsecticides. The infective propagules known as conidia produced by the entomopathogenic fungi was mass-produced using semi-solid fermentation to be used as an active ingredient in a mycoinsecticidal product. The aims of this study was to formulate the conidia as water-dispersible granules (WG), to delve into WG formulation methods, and to evaluate the factors that influence the biological and physical performances of the WG-conidia formulations in both laboratory and glasshouse conditions. The study initiated with the screening for the best entomopathogenic fungal isolate to be used as active ingredient. Five fungal isolates i.e. Metarhizium anisopliae (MPs, MaBg and MaCc1a), Beauveria bassiana (BbGc) and Paecilomyces fumosoroseus (PfPx) were screened by exposing each isolate’s conidia to wet-heat and oven-heat stress through a series of temperatures. Isolate MPs showed the best tolerance to the heat stresses and was selected as the active ingredient in all WG-conidia formulations. Inert ingredients and/or additives were then selected based on the ability of the conidia of MPs to survive more than 80% germination upon contact with each ingredient at different temperatures and exposure duration. Following the selection of inert ingredients and/or additives, ternary phase diagrams were constructed to obtain five ‘Surfactant systems’, in which a total of 22 different WG-conidia formulations were prepared. All 22 formulations were tested and rated for their physical and biological performances using four parameters i.e. conidial fresh viability, viability after 7 days in storage, suspensibility, and dispersibility. Five formulations were rated as ‘Good’, 12 formulations as ‘Satisfactory’ and five was ‘Unsatisfactory’. Six WG-conidia formulations containing additives were selected and tested for their storage stability at different temperatures and exposure period. Results showed that shelf life of WG-conidia formulations were greatly reduced when storage temperature and exposure period increased. Shelf life improved when additive(s) was added to the formulations. Formulations containing sodium alginate and sodium acetate showed better conidial germination (80%), 15 days after formulation (DAF) at 15°C, than formulations without additives. While the formulation containing sodium alginate showed 27% conidial germination at 30DAF, 15°C, most WG-conidia formulations did not store well beyond this period and temperature. The effectiveness of the WG-conidia formulation was evaluated through a time-mortality response bioassay against the insect pests of economic importance in Malaysia, Plutella xylostella and Epilachna indica. The WG-conidia formulation, 3B5gK, was comparatively satisfactory to unformulated conidia in causing death to both insect pests with median lethal time (LT50) of 6.5 days and 5 days for P. xylostella and E. indica, respectively. Relative potency of unformulated conidia was 1.3-1.6 times than that of 3B5gK. In a pre-field trial conducted in the glasshouse to investigate the effects of different volume application rates of WG-conidia formulations on the larvae of P. xylostella, the formulation containing sodium alginate, 7A5gBAl caused the quickest mortality of larvae (LT50=72 hours) at high volume application rate compared to three other WG-conidia formulations and unformulated conidia. Most WG-conidia formulations showed potential to be further developed as mycoinsecticidal products due to their good biological potency and physical performances in both laboratory conditions and pre-field application. However, further studies should be done to improve shelf lives of the product and their applicability in reduced cost, which are imperative factors for any microbial products to be acceptable by end users.